An outline of the impact of trade unions of professional athletes on the conditions of employment in professional sport of the United States - Pałucka, Daria (Journal of Education, Health and Sport, 2017)
The article concerns the activities of trade unions of professional athletes in the United States. The main problem is the impact of the union on the standards of hiring players. This effect is visible in particular in the so-called collective bargaining aimed at achieving consensus in the form of a collective bargaining agreement. Collective agreements contain a number of provisions governing the employment of players. Of particular note are the so-called standard players contracts, which are the mandatory model of a contract between a player and a club. By presenting the outline of the problem of the decertification of the trade union, the role of union and collective agreements in shaping the organization of competition within a given sport discipline is presented.